Worldwide short selling regulations and IPO underpricing - Boulton, Thomas J.; Smart, Scott B.; Zutter, Chad J. (Journal of Corporate Finance, 2020)
We study the impact of country-level short selling constraints on IPO underpricing. Examining 17,151 IPOs from 36 countries, we find that IPO underpricing tends to be greater in countries that ban short selling or security lending and in countries where short selling is not practiced. Non-positive first-day returns are more common in countries where short selling is allowed, security lending is allowed, and short selling is commonly practiced. Short selling constraints exacerbate the positive relation between investor sentiment and underpricing. Additional evidence suggests that higher quality information environments may partially alleviate the effects of short sale constraints on underpricing.